Investigation of the Relationships between Stoma Resistance and Soil Water Matric Potential with other Environmental Factors in Respect of Mathematical Modelling of Plant Water Consumption - MUJDECI, METIN; SARIYEV, ALHAN; CELIK, ISMAIL; TULUN, YUSUF; KARACA, HUSEYIN (Asian Journal of Chemistry, 2010)
The stoma resistance influences the determination of the transpiration, which is one of the main components of the water balance in the soil and which is one of the morphological properties of the plants. Stoma in the plants control plant water consumption by the cells key doing the functions of closure and disclosure of the apertures through their original structures. In this respect, in the pot experiments which were carried out in a greenhouse conditions, the matric potential of the soil water and plant stoma resistance together along with the other environmental factors were investigated. In this study, using Seri-82 and Adana-99 wheat varieties the matric potential of the soil water and the stoma resistance values at the field capacity and the low moisture levels were measured. In the study, it was observed that the plant stoma resistance was influenced rapidly by the matric potential of the soil water. Although the stoma resistance at the limits of soil water field capacity was found at the limits of 0.69-4.74 s cm-1, the stoma resistance showed increments at the intervals of 7.6-54.8 s cm-1 against the increasing soil water tension.